On Newstead Abbey - Brown, Simon (Romanticism on the Net, 2023)
Newstead Abbey is a reliquary of many, many stories from Lord Byron’s time in residence and the centuries before and after. Each generation has left its mark on the house, but the centrepiece of the site’s history will always be Byron. Inspired by and fascinated with its already ancient history, the poet left an indelible mark on everything that has happened there since.